Kepastian Hukum Pendaftaran Merek Sebagai Upaya Perlindungan Kepemilikan Hak Atas Merek - Febriyanti, Susanty (Prodi Hukum S1 - Fakultas Hukum - Universitas Pamulang, 2025)
Brands are a crucial part of the world of commerce. Brands help consumers recognize a manufacturer's products. They serve as a means of identifying the origin of the goods or services they produce. For eyeglass manufacturers, brands serve as a guarantee of the value of their products, particularly regarding product quality. Traders use brands to promote their merchandise and expand their market. For consumers, brands are essential in making informed product choices. It's unimaginable that a product without a brand would be unknown to consumers. Registration of a brand determines the legal relationship between a person or legal entity and a brand as a matter of legal protection for the intellectual property rights of that person or legal entity. The legal relationship between a person and a brand is included in the legal relationship of a person's intellectual property rights which must be protected by the state by providing legal protection to protect a person's rights. Public awareness, both individuals and legal entities, to apply for trademark registration used in goods and or services is increasing from year to year. The increase in applications for trademark registration used in goods and or services is related to the rapid development of economic activities and the high level of business competition among business actors. The very rapid progress of information technology and transportation in the era of globalization allows goods or services produced and marketed in one country, within a short period of time, to be marketed in other countries. By using internet media, marketing of goods or services no longer recognizes time and country boundaries.